2013
DOI: 10.1620/tjem.230.227
|View full text |Cite
|
Sign up to set email alerts
|

Serum Decoy Receptor 3 Is a Useful Predictor for the Active Status of Chronic Hepatitis B in Hepatitis B e Antigen-Negative Patients

Abstract: Hepatitis B virus (HBV) infection is a global public health problem, because patients with chronic hepatitis B (CHB) may progress to liver cirrhosis and eventually evolve into hepatocellular carcinoma. Decoy receptor 3 (DcR3) is a soluble receptor of the tumor necrosis factor receptor superfamily, and has been implicated in anti-apoptotic and anti-inflammatory pathways. In this study, we explored the clinical value of serum DcR3 in predicting the active status of CHB in hepatitis B e antigen-negative patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…In other words, DcR3 is easily detectable in the blood serum of patients, raising the possibility of using DcR3 as a biomarker for diagnosis, treatment and prognosis of some diseases. Therefore, in this study, DcR3 expression in serum was detected, showing that DcR3 in serum from HCC patients was higher than that in serum from humans without HCC, in keeping with the findings of Yanqiang Hou and Giorgos Bamias 33,34 . These observations indicate that DcR3 plays an important role in HCC progression and may serve as a valuable biomarker for monitoring HCC development in humans.…”
Section: Discussionsupporting
confidence: 90%
“…In other words, DcR3 is easily detectable in the blood serum of patients, raising the possibility of using DcR3 as a biomarker for diagnosis, treatment and prognosis of some diseases. Therefore, in this study, DcR3 expression in serum was detected, showing that DcR3 in serum from HCC patients was higher than that in serum from humans without HCC, in keeping with the findings of Yanqiang Hou and Giorgos Bamias 33,34 . These observations indicate that DcR3 plays an important role in HCC progression and may serve as a valuable biomarker for monitoring HCC development in humans.…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, two recent studies may support this possible role of DcR3 in the inflammatory/fibrotic pathway. It was reported that DcR3 concentrations were increased in patients with primary biliary cirrhosis in both local and systemic levels when compared to healthy controls [21], while researchers from Japan suggest that sDcR3 values may be helpful in differentiating between active and inactive chronic hepatitis B in the subgroup of hepatitis B e antigen-negative patients [22]. Furthermore, in our study, within the population of patients with chronic hepatitis, the highest DcR3 values were seen in those with advanced Ishak scores in liver biopsy (i.e., with increasing levels of fibrosis).…”
Section: Discussionmentioning
confidence: 99%
“…While the elevated DcR3 in ACLF is not reported previously, an increased DcR3 has been observed in patients with chronic HBV infection and is also suggested to be a useful noninvasive biomarker for discrimination of active hepatitis B from inactive HBV carriers [25] and a marker for liver fibrosis [26]. The pathophysiological value of increased DcR3 might be related with its function of modulating immune response, disrupting Fas signaling, and suppressing apoptosis.…”
Section: Discussionmentioning
confidence: 99%